Pemberdayaan Masyarakat Kota Daro 2 Kecamatan Rantau Panjang Melalui Pelatihan Pembuatan Cuko Pempek Bernilai Gizi - Nico Syah Putra; Asep Dodo Murtado; Alhanannasir Alhanannasir; Mukhtarudin Muchsiri; Dasir Dasir; Suyatno Suyatno; Rika Puspita Sari MZ; Ade Vera Yani; Idealistuti Idealistuti (Universitas Muhammadiyah Palembang, 2025)
ABSTRACT. Cuko pempek is a local food from South Sumatra, especially Palembang City, with potential and high sales value, especially when packaged well and attractively. Community empowerment in Kota Daro 2 Village was carried out to develop a bottled cuko pempek business. This program focused on training in making bottled cuko pempek using key lime acid, which has great potential to improve the village community's economy. The implementation method included field observation, interviews, and direct practice, starting with the introduction of ingredients and processing to product packaging. Twenty housewives and village youth participated in this activity. The results demonstrated that the community successfully practiced making cuko pempek with consistent taste quality and more hygienic packaging. Value-added analysis indicated that the production of 30 bottles of cuko provided a profit of 1.5 times the capital, making it feasible to develop as a home business. The implementation of offline and online marketing strategies expanded the product reach, while a SWOT analysis identified outstanding potential as well as challenges in developing a nutritious cuko pempek business. Overall, this activity succeeded in increasing community understanding to open up business opportunities selling cuko pempek in bottles as a sustainable economic source in Kota Daro 2 Village.